Self-care behaviors in high-risk women for breast cancer: A randomized clinical trial using health belief model education - Maryam Damghanian; Habibollah Mahmoodzadeh; Zohreh Khakbazan; Behjat Khorsand; Mohadese Motaharinezhad (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Breast cancer is the most common cancer in Iranian women. The number of people with this disease is increasing across the world. Positive family history is one of the risk factors for developing breast cancer. However, early detection is the main method to fight this disease. This study was conducted to examine the effect of education based on the health belief model (HBM) on self-care behaviors among first-degree relatives of patients with breast cancer. METHODS: This clinical trial was conducted in 2016 on 80 women in Tehran city, Iran. Data were collected using a three-part questionnaire regarding demographic data, the HBM, and self-care behaviors. The educational program based on the HBM was held in 4 ninety-minute training sessions through lectures, group discussions, question and answer, image presentations, and PowerPoint presentations. The questionnaires were completed before and 2 months following the intervention by intervention and control groups. Data were analyzed using descriptive and inferential statistics through the SPSS16 software. RESULTS: The mean score of the HBM constructs before the intervention in the groups had no statistically significant differences (P > 0.05). Eight weeks after the intervention, the mean score of the constructs of the HBM in the intervention group significantly increased and a statistically significant increase in the mean score of self-care in the intervention group compared to the preintervention was found, so that the self-care behavior score in the intervention group was 0.69 ± 0.09 before the intervention and was changed to 0.74 ± 0.09 after the intervention (P < 0.0001). CONCLUSION: Our results suggest that education based on the HBM was effective in promoting self-care behaviors among first-degree relatives of breast cancer patients. Therefore, education based on HBM may have an important implication for breast cancer prevention in Iran.